2019
DOI: 10.1155/2019/8043415
|View full text |Cite
|
Sign up to set email alerts
|

Highly Soluble Drugs Directly Granulated by Water Dispersions of Insoluble Eudragit® Polymers as a Part of Hypromellose K100M Matrix Systems

Abstract: The aim of the present study was to investigate the suitability of insoluble Eudragit® water dispersions (NE, NM, RL, and RS) for direct high-shear granulation of very soluble levetiracetam in order to decrease its burst effect from HPMC K100M matrices. The process characteristics, ss-NMR analysis, in vitro dissolution behavior, drug release mechanism and kinetics, texture profile analysis of the gel layer, and PCA analysis were explored. An application of water dispersions directly on levetiracetam was feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
5
0
1
Order By: Relevance
“…It was evident from the formulations F1 and F4 that with the increase in the concentration of the plastic polymer, the drug release rate was found to be significantly decreased (p<0.05, one-way ANOVA) due to the increase in the density of the plastic polymer as well as owing to the difficulty in permeation of water into the plastic matrix at high amounts of the matrix polymers. The obtained results were correlated with those reported by Maskova E et al [23].…”
Section: Effect Of Amount Of Plastic Polymerssupporting
confidence: 92%
See 1 more Smart Citation
“…It was evident from the formulations F1 and F4 that with the increase in the concentration of the plastic polymer, the drug release rate was found to be significantly decreased (p<0.05, one-way ANOVA) due to the increase in the density of the plastic polymer as well as owing to the difficulty in permeation of water into the plastic matrix at high amounts of the matrix polymers. The obtained results were correlated with those reported by Maskova E et al [23].…”
Section: Effect Of Amount Of Plastic Polymerssupporting
confidence: 92%
“…The rate constant values were showed in the table 3. This could be attributed to the degree of permeability of water by the polymer into the plastic polymer matrix [21][22][23]. With the increase in the permeability of water into the plastic matrix, the diffusion of the drug from the plastic matrix increases and vice versa.…”
Section: Effect Of Type Of Plastic Polymermentioning
confidence: 99%
“…The crosslinked alginate gel matrix was incapable of delaying diffusion of quercetin, following rapid dissolution from the quercetin/PVPK30 solid dispersion. Several studies have reported that the burst release effect may be reduced by increasing the concentration of polymer in the delivery system ( Chakraborty et al, 2009 , Mašková et al, 2019 ). However, the alginate solution concentration was limited to 2% w/v in the present study due to the resulting high viscosity.…”
Section: Resultsmentioning
confidence: 99%
“…Eudragit ® RS100 (RS) and RL100 (RL) are copolymers of poly(ethylacrylate, methylmethacrylate and chlorotrimethyl-ammonioethyl methacrylate), containing an amount of quaternary ammonium groups between 4.5 and 6.8% and 8.8 and 12% for RS and RL, respectively. Both are insoluble at physiological pH values and capable of swelling [22], thus representing good materials for the dispersions of drugs [23,24].…”
Section: Introductionmentioning
confidence: 99%